Measuring and Modelling of the Traffic Flow at Microscopic Level - Čop, Rudi; Batista, Milan (Promet - Traffic&Transportation, 2004)
The traffic flow theory is dealing with the better understandingof the traffic flow and its improvement. Most often, the researchedsubject was been the road traffic. It is namely thatheavy traffic and traffic jams are the frequent phenomena onthe roads.The traffic flow theory incorporates the different areas ofknowledge necessary to establish a successful traffic-flow simulationmodel. Good correlation between the simulation modelresults and data collected in the open road conditions are notthe only conditions which are necessary to approve the simulationmodel as accurate. The obtained simulation results may beused for the improvement of traffic conditions, only if themodel obeys the classical laws of physics.This paper is dealing with the simple microscopic model fortwo-vehicle-platoon behaviour in the traffic flow. The model isbased on solving of the delay differential equations. The simulationmodel results have been compared with the measurementresults. The comparison has enabled assessment of the selectedsimulation model to check whether it would be goodchoice for further traffic-flow researches at the microscopiclevel.